PENGEMBANGAN MEDIA AUDIO VISUAL BERBASIS VIDEO ANIMASI CANVA PADA MATA PELAJARAN INFORMATIKA - Dyan Yuliana; Siti Seituni; Nurin Kartika Wahyuningsih (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2025)
In improving the quality of computer science learning in schools, the use of audio-visual media has proven to be effective in increasing student understanding. one of them is a lack of learning resources, difficulty remembering, lack of student concentration when studying, student participation in learning is still not visible, one of the factors that makes students bored when carrying out learning activities so that students do not listen to the teacher who is explaining. The solution is that one of the tools that has emerged as a solution for creating attractive and easily customizable visual content is Canva animated videos. The aim of this research is to determine the level of suitability of Canva-based learning media in Informatics subjects. The method in this research is development research (Research and Development). The data collection technique used is expert validation testing. The results of the validation of the suitability of Canva media by media experts obtained a score of 93.7% in the "very suitable" category, the results of the material expert's assessment obtained a score of 84% in the "very suitable" category, and the results of the assessment from students obtained a score of 98% in the category “very suitable”. So, it can be concluded that audio visual learning media based on Canva animated videos is suitable for use in the Informatics subject, class VII data structure material at SMP Plus As'adiyah.